Social identity positively impacts sustainable behaviors of backpackers. Issue 1 (2nd January 2023) - Agyeiwaah, Elizabeth; Pratt, Stephen; Iaquinto, Benjamin Lucca; Suntikul, Wantanee
Abstract: While backpacker social identity remains an important theme among tourism researchers, its influence on sustainable behaviors has received limited attention. We examine the impact of backpacker social identity on sustainable behavior based on both a structural modeling approach and regression analysis. A survey of 400 backpackers is conducted within Cape Coast, a major tourism hub in Ghana, West Africa. Supporting seven out of eight hypotheses based on PLS-SEM, social identity has a positive effect on sustainable behavior, which in turn positively affects satisfaction suggesting that the more backpackers identify themselves with this group the more sustainably they behave. Additionally, social identity has a negative impact on unsustainable behavior which negatively impacts behavioral intentions. These findings suggest that individuals who identify themselves as backpackers are less likely to engage in unsustainable behavior. Findings contribute to a deeper understanding of the nexus between backpacker social identity and sustainable behavior.